Implementasi Kebijakan Penilaian Kepatuhan oleh Ombudsman RI Perwakilan Sumatera Barat - Mayang Ratu Susandra; Desna Aromatica; Hendri Koeswara (Universitas Sultan Ageng Tirtayasa, 2024)
This research is motivated by the routine agenda of the Ombudsman Republic Indonesia every year to assess the implementation of public services which is a priority agenda in the 2020-2024 RPJMN. This research aims to see how the implementation of compliance assessments is carried out by the Indonesian Ombudsman Representative of West Sumatra Province. This research uses a descriptive qualitative approach by collecting data through interviews, documentation and observation from purposive sampling informants. The theory used in this research is policy implementation according to Edwards III which consists of communication, resources, disposition and bureaucratic structure. The results of this research indicate the implementation of compliance assessments has gone well. In the communication variable, the implementation of the compliance assessment has been communicated. However, the clarity of the information contained in the relevant regulations is not yet complete considering that there has been an update to aspects of the assessment carried out by the Ombudsman. In the resource variable there is a shortage of human resources which are insufficient in quantity but can be balanced in terms of quality. The disposition variables and bureaucratic structure have been running well. Thus, the compliance assessment carried out by the Indonesian Ombudsman Representative for West Sumatra had a positive influence on public services in West Sumatra Province. With the role of the Ombudsman, the compliance status obtained by West Sumatra Province is increasing every year.